Automatic control of home appliances based on SCADA and IoT system - Ahmed, Riffat; Ananta, Khandaker Towfiqul Islam; Anwar, Mohammed Fardin; Afrin, Samanta (Brac University, 2022)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2021.